Association between Serum Vitamin D Level and Parkinson’s Disease: Case Control Study in a Tertiary Level Hospital, Bangladesh - Rahman, Aminur; Ahmed, Muhammad Jamil; Russel, Abul Hasnat Md; Hossain, Md Alamgir; Huq, Mohammed Nazmul; Khan, Shahjada Mohammad Dastegir; Rahman, Md Moshiur; Paul, Biplab; Saha, Pallab Kanti (Bangladesh Journal of Medicine, 2024)
Background: Parkinson's disease is a neurodegenerative disorder that is frequently observed in individuals who are 50 years of age or older. The etiology of this disease is still unknown, but research has shown the influence of factors like vitamin D acting as a hormone in Parkinson's disease. The current study aimed to explore the association between serum vitamin D levels and Parkinson's disease. Methods: In 2019 to 2020, the current researchers conducted this case control study on 50 patients with Parkinson’s disease and 50 healthy subjects as the control group in the department of Neurology of Sir Salimullah Medical College & Mitford Hospital, Dhaka, Bangladesh. Demographic information (age, gender, and education), serum levels of vitamin D in the two groups, disease duration, disease severity, and cardinal features of the disease in the patient group were investigated. Data were analyzed using the SPSS 23 software with the t-test, Kruskal Wallis, Mann-Whitney, and adjusted logistic regression. Results: The mean age of cases was 72.30 ±454 and the control group had a mean age of 60.08±8.305. Regarding the symptoms of the cases tremor 30 (60%), rigidity 5 (10%), bradykinesia 12 (24%) and postural instability 3 (6%) and regarding disease duration (y) <5 years-26 (52%), 5 to 10 years-17 (34%), >10years 7 (14%) and disease severity 1 to 2.5 – 26 (52%) , 2.5-to-3 -18 (36%) and >3 – 6 (12%) Serum vitamin D levels of males were 17.70±6.06 ng/mL in patients and 30.31±5.59ng/mL in control groups, respectively which is clinically significant. Serum vitamin D levels of females were 20.03±5.75ng/mL in patients and 28.53±6.31ng/mL in control groups, respectively, which is clinically significant (P = 0.001). For the participants under 60 years of age, the mean serum vitamin D levels were 27.70±0.00 ng/mL and 30.78±5.44 ng/mL in patient and control groups, respectively. In participants aged 60 and older, the mean serum vitamin D levels were 18.40±5.91 ng/mL and 28.13±6.26 ng/mL in patient and control groups, respectively. These diﬀerences were statistically signiﬁcant (P=0.001).Logistic regression analysis with adjusted demographic variables showed that the observed lower levels of serum vitamin D in cases compared with the control group was statistically signiﬁcant(OR=4.17;95% CI:1.37,12.71;P=0.012). Conclusion: There was a signiﬁcant relationship between low serum vitamin D and Parkinson’s disease. Bangladesh J Medicine 2024; 35: 180-186